Surgical resection of a ruptured transverse pancreatic artery aneurysm - Toru Takematsu (Surgical Case Reports, 2021)
Abstract Background Visceral artery aneurysms are rare, but they may cause heavy bleeding and high mortality. In addition, aneurysms originating from the superior mesenteric artery (SMA) account for only 1% of visceral artery aneurysms. We report the rare case of a ruptured transverse pancreatic artery aneurysm originating from the SMA that required urgent surgical treatment. Case presentation A 66-year-old woman presented with acute back pain after lunch, and she was transported by ambulance. She had upper quadrant spontaneous pain and moderate tenderness, but no guarding or rebound pain. She had rheumatoid arthritis, and was taking 10 mg of steroids per day. Contrast-enhanced computed tomography demonstrated a retroperitoneal hematoma spreading to the ventral side of the left kidney and extravasation of contrast agent from a branch of the SMA. We diagnosed rupture of aneurysm. We conferred with our IVR team on treatment strategy for the ruptured aneurysm. In addition, we finally selected operation, since the branch of the SMA to the aneurysm was too thin and complex to conduct IVR. For this reason, we performed emergency simple aneurysmectomy of the transverse pancreatic artery. The postoperative course was relatively smooth. Conclusion Rupture of a transverse pancreatic artery aneurysm originating from the SMA is rare. However, when diagnosing patients with acute abdomen or back pain, we should consider rupture of a visceral artery aneurysm. Endovascular treatment may currently be common for ruptured visceral artery aneurysms, but we should flexibly treat them according to the patient’s condition and facility considerations.